Research on the Quality Improvement of Automatic Tone Adjustment Technology for Movie Images Using Computer Vision Algorithms - Cui, Bingshuoshi (Applied mathematics and nonlinear sciences, 2024)
Color plays an indispensable role in the formation of movie style, and hue, as an important part of color, plays a pivotal role in the study of the quality of movie pictures. The study is based on the basic theory of the color and color space of the movie picture, equalizing the histogram of the movie picture, and then combining the HistoGAN network and Laplace algorithm of computer vision algorithms to realize the enhancement of the hue of the movie picture, and then adjusting and improving the quality of the movie picture automatically. Taking 10 comedy movies by Wes Anderson as an example, the movie tones are measured and counted. According to the results, the movie screen tones adjusted have a strong ability to convey image details and have better contrast and clarity enhancement effects while maintaining image fidelity. As the year progresses, the brightness of the adjacent period in Wes Anderson’s comedy movies becomes more frequent and larger after the movie screen hue is adjusted. The overall of his movies is the color matching law of warm tones with larger saturation with cooler tones with smaller saturation, and the hue adjustment gives the movie screen a more advanced sense of beauty.